Avaliação mutagênica e antimutagênica do extrato aquoso de Mimosa hostilis Benth pelo Teste de Mutação e recombinação somática em asas de Drosophila melanogaster (SMART) - Lima, Adiles Paulo de (2010)
The plant Jurema preta (Mimosa hostilis) is traditionally used in semi-arid regions of Brazil, for painkillers and anti-inflammatory, in the form of tea from bark. Despite the use of plants with medicinal purposes is part of the knowledge already popularized long, detailed studies about the action of the constituents in the organisms need further investigation, because know that difference of doses lead to damage to health. Phytochemical studies of compounds of some species of the genus Mimosa (Mimosa pudica and Mimosa rubicaulis) showed antioxidant activity, toxicological and bactericidal, depending on the dose applied, but very little is known about the likely effects mutagenic and/or antimutagenic of Mimosa hostilis. In attempt to occupy this gap, this study aims to investigate the mutagenic and protective effect of tree concentrations of aqueous extracts of Mimosa hostilis (3,91, 15,625 e 62,5 mg/mL) through the SMART technique (Somatic Mutation and Recombination Test) of wing through 2 crosses standard (ST) and high bioactivation (HB) in 3 strains of Drosophila melanogaster: multiple wing hairs (mwh), flare 3 (flr3) and Oregon R / flr3 (ORR/flr3). The results showed mutagenic and antimutagenic in concentrations tested. The antagonistic effects (mutagenic and antimutagenic) observed is a reflection of the constitution phytochemical complex of M. hostilis aqueous extract, where individual and synergistic effects of its components can be related directly or indirectly with the potential mutagenic and antimutagenic matches. However, it is important to identify which of these components, alone or combined, are responsible for the data presented here, to the best use of the plant as herbal medicine.